Marine Environmental Suitability Mapping for Lobster Sea-cage Culture in East Lombok Using Remote Sensing Data and GIS Approaches - Sarah N.F., Zealandia; Rivani, Anggia; Puspitasari, Bety; Ikhwansyah, Firdian; Maulidyah, Fonna; D, Ridho Dwi; P, Sufiyana Eka; Widyatmanti, Wirastuti (Indonesian Aquaculture Society (MAI), 2016)
Lobster, one of the high values sea-cage culture commodities in Indonesia, has some specific requirements of life environment. However, there haven’t been any studies that specifically identify these potential sites. Until today it is only 3.50 ha out of 526.86 Ha of these that have been utilized. This study aims to map the marine suitability environment for lobster cultivation in Ekas Bay, using remote sensing and GIS approaches. The requirement parameters maps for lobster marine suitability, includes oxygen levels (DO), nutrition, salinity, temperature, depthness, pH, and water clearence which are able to be extracted from Landsat 8 imagery. Using GIS, a model was developed to integrate those maps with marine environment secondary maps, water laboratory analysis, and other information from interview result with the local farmer’s. The result shows that lobsters live in the environment which has the temperature between 200 to 250C and at the water depth of reaching 100 m. Laboratory analysis result presents the pH value of above 7 in average, DO ranges from 5-8 ppm, and salinity level from 28 to 35 ppt. In summary, the integration of remote sensing and GIS approaches are able to identify the common parameter that support the environment suitability for lobsters which is then formulated as a standard of marine environment suitability mapping.